3D‐printed Current Collector Plates: Simulation and Performance Evaluation in a Mini Fuel Cell. Issue 6 (21st November 2018) - Cano‐López, J. A.; Ortega‐Díaz, D.; Duarte‐Moller, A.; Encinas, A.; Dector, A.; Olivares‐Ramírez, J. M.
Abstract: This paper describes the construction of 3D‐printed current collectors used in the fabrication, simulation and performance evaluation of four mini proton exchange membrane (PEM) fuel cells. These fuel cells comprised of acrylonitrile butadiene styrene‐printed current collector plates using different flow channel designs: pin, spiral, serpentine and radial. In this work, we demonstrated that the mini PEM fuel cells were capable of converting fuel to current according to computational fluid dynamics, which was used to carry out the optimization of the geometry of the current collector plates. The correlation between the mass transfer and the power density is discussed, and the largest mass transfer is reported for the pin geometry, which also yielded the higher power values compared to the spiral, serpentine and radial geometries (9.9, 9.0, 9.0, and 8.2 mW cm −2, respectively). These low‐cost devices should be useful for portable applications.